Burning our Boats - Perera, Suvendrini (2015)
‘At the unstable point where the 'unspeakable' stories of subjectivity meet the narratives of history, of a culture . . .’ Stuart Hall (1932-2014). The burning of boats, that classic figure for the impossibility of return, was, for over a decade a practice routinely staged by the Australian state as a form of ‘deterrence’ against other unwanted entrants – even as it served, for those just landed, to confirm the finality of their arrival. More recently, this official “torching rite” of no return meets its counterpart in the bizarre logic of the “orange lifeboat,” where asylum seekers are forcibly turned back to an uncertain fate aboard unsinkable, air-conditioned capsules. This paper considers questions of arrival, departure and refugee and diasporic subjectivities in the context of Australian refugee policy. Some readers may notice in my subtitle an allusion to V.S. Naipaul’s memoir, The Enigma of Arrival, but more immediate to my concerns is Amitav Ghosh’s articulation of a distinction between exodus and dispersal narratives. Whereas narratives of exodus fix their gaze on the shore of arrival, Ghosh suggests, dispersal compels a return to the pain of rupture and the movement of departure: the sting of smoke evermore in our eyes from our burning possessions; before us, the steady flaming of our boats. Marking Stuart Hall’s indispensable theorizing of diasporic subjectivities in the wake of his passing earlier this year, I ask how refugee and disapora bodies and subjects are made and unmade in the context of the Australian borderscape, understood as a set of makeshift, protean geographies of making live and letting die.